The Relation Between Brain Amyloid Deposition, Cortical Atrophy, and Plasma Biomarkers in Amnesic Mild Cognitive Impairment and Alzheimer’s Disease - Fan, Ling-Yun; Tzen, Kai-Yuan; Chen, Ya-Fang; Chen, Ta-Fu; Lai, Ya-Mei; Yen, Ruoh-Fang; Huang, Ya-Yao; Shiue, Chyng-Yann; Yang, Shieh-Yueh; Chiu, Ming-Jang (Frontiers in Aging Neuroscience, 2018)
Background: Neuritic plaques and neurofibrillary tangles are the pathological hallmarks of Alzheimer’s disease (AD), while the role of brain amyloid deposition in the clinical manifestation or brain atrophy remains unresolved. We aimed to explore the relation between brain amyloid deposition, cortical thickness and plasma biomarkers. Method: We used 11C-Pittsburgh compound B-positron emission tomography to assay brain amyloid deposition, magnetic resonance imaging to estimate cortical thickness and an immunomagnetic reduction assay to measure plasma biomarkers. We recruited 39 controls, 25 subjects with amnesic mild cognitive impairment (aMCI) and 16 subjects with AD. PiB positivity (PiB +) was defined by the upper limit of the 95% confidence interval of the mean cortical SUVR from 6 predefined regions (1.0511 in this study). Main results: All plasma biomarkers showed significant between-group differences. The plasma Aβ40 level was positively correlated with the mean cortical thickness of both the PiB + and PiB - subjects. The plasma Aβ40 level of the subjects who were PiB + was negatively correlated with brain amyloid deposition. In addition, the plasma tau level was negatively correlated with cortical thickness in both the PiB + and PiB - subjects. Moreover, cortical thickness was negatively correlated with brain amyloid deposition in the PiB + subjects. In addition, the cut-off point of plasma tau for differentiating between controls and AD was higher in the PiB - group than in the PiB + group (37.5 versus 25.6 pg/ml, respectively). Lastly, ApoE4 increased the PiB + rate in the aMCI and control groups. Conclusion: The contributions of brain amyloid deposition to cortical atrophy are spatially distinct. Plasma Aβ40 might be a protective indicator of less brain amyloid deposition and cortical atrophy. It takes more tau pathology to reach the same level of cognitive decline in subjects without brain amyloid deposition, and ApoE4 plays an early role in amyloid pathogenesis.